Crossed Pontine Hemiatrophy Associated with Unilateral Cerebellar Hemorrhage in Premature Infants - Parodi, Alessandro; Ramenghi, Luca A.; Malova, Mariya; Tortora, Domenico; Severino, Mariasavina; Morana, Giovanni; Rossi, Andrea (Neuropediatrics, 2016)
Background Cerebellar hemorrhage is a complication of extreme prematurity with a significant impact on the neurodevelopmental outcome. It has been shown that cerebellar hemorrhage is associated with a reduction in the anteroposterior diameter of the pons on the midline sagittal plane at term-equivalent age, suggesting that cerebellar injury may impair overall pons development in premature infants.Objective This study stemmed from an incidental observation of crossed pontine hemiatrophy in a preterm infant with a history of unilateral massive cerebellar bleeding. We aimed to verify the presence of this association in a population of preterm infants.Methods Among all, very preterm infants (GA < 32 weeks) born at our institution over a 6-year period, those with a diagnosis of unilateral massive cerebellar hemorrhage were selected. Magnetic resonance imaging scans of the selected subjects were reviewed.Results Six patients with unilateral massive cerebellar hemorrhage were identified. MRI showed crossed hemiatrophy of the pons in all cases.Conclusion Crossed hemiatrophy of the pons was associated with massive unilateral cerebellar hemorrhage. This finding may reflect retrograde degeneration of pontocerebellar fibers and loss of neurons in contralateral hemipons.
Keywords: cerebellar hemorrhage; pons; MRI; prematurity